Antagonistic roles for Ultrabithorax and Antennapedia in regulating segment-specific apoptosis of differentiated motoneurons in the Drosophila embryonic central nervous system. - Rogulja-Ortmann, A.; Renner, S.; Technau, G.M. (Development, 2008)
The generation of morphological diversity among segmental units of the nervous system is crucial for correct matching of neurons with their targets and for formation of functional neuromuscular networks. However, the mechanisms leading to segment diversity remain largely unknown. We report here that the Hox genes Ultrabithorax (Ubx) and Antennapedia (Antp) regulate segment-specific survival of differentiated motoneurons in the ventral nerve cord of Drosophila embryos. We show that Ubx is required to activate segment-specific apoptosis in these cells, and that their survival depends on Antp. Expression of the Ubx protein is strongly upregulated in the motoneurons shortly before they undergo apoptosis, and our results indicate that this late upregulation is required to activate reaper-dependent cell death. We further demonstrate that Ubx executes this role by counteracting the function of Antp in promoting cell survival. Thus, two Hox genes contribute to segment patterning and diversity in the embryonic CNS by carrying out opposing roles in the survival of specific differentiated motoneurons.